CORRELATION ТIME ELECTROCSRDIOGRAPHIC INDEXES WITH CONSTITUTIONAL CHARACTERISTICS - Sarafynuk, L.A.; Kyrychenko, Y.V.; Belik, N.V.; Boreyko, T.I. (World of Medicine and Biology, 2014)
The article features established correlations between time ECG parameters in the first and second standard leads and anthropometric dimensions, components of somatotype and body mass indices and carpal dynamometry class athletes and nonsportsmen adolescence.
Keywords: correlation; electrocardiography; anthropometry; somatotype; components of body weight; athletes; youth